PROFOUND VISUAL RECOVERY AT 16 MONTHS AFTER RESOLUTION OF SEROUS RETINAL DETACHMENTS SECONDARY TO THROMBOTIC THROMBOCYTOPENIC PURPURA: CASE REPORT AND LITERATURE REVIEW. Issue Volume 15:Issues 1(2021) (2021) - Williams, Parker J.; Pearce, William A.; Smith, Jesse M.; Robinson, Joshua
Abstract : Purpose: To report a unique case of dramatic improvement in objective visual function during the recovery phase, after resolution of thrombotic thrombocytopenic purpura–related serous retinal detachments and to review prognostic trends in reported cases involving the macula. Methods: Observational case report and literature review. Results: A 36-year-old white woman with thrombotic thrombocytopenic purpura developed vision loss from serous retinal detachments in both eyes. Over a 16-month period, after both retinae remained attached, best-corrected visual acuity improved from 20/400 to 20/50 in both eyes with dramatic improvement on optical coherence tomography and autofluorescence imaging. Conclusion: Although thrombotic thrombocytopenic purpura is a life-threatening illness, visual prognosis in patients with macula off serous retinal detachments appears excellent. Most cases reviewed in literature improved to baseline visual acuity, but recovery periods ranged from days to many months. Hyperautofluorescent granularity on autofluorescence photography may be an indicator of chronic retinal detachment and a more delayed visual recovery. Abstract : A case report and literature review of serous retinal detachments related to thrombotic thrombocytopenic purpura with prognostic signs that may contribute to clinicians' understanding of visual recovery from this rare disease process.